1995
DOI: 10.1177/135050689500200306
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Masculinity

Abstract: Investigating women and technology may seem like a paradoxas technology is a word with masculine connotations. Feminists have made efforts to correct this image by revealing that women do in fact work with technology, as users and also as inventors. The problem is that such activities on the part of women are made invisible. But the question remains why they become invisible. Is the answer that technology is so closely connected to men and masculinity that activities within this field are categorized as someth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…The tractor is therefore a strong masculine symbol (Brandth 1993). Lie (1991Lie ( , 1992 has shown that because technology functions as a symbol of masculinity, it becomes a vital source of masculine gender identity. Machines are a part of the picture men show of themselves, and the machines tell us that the persons are in possession of qualities required for a man (Lie 1992).…”
Section: Technology and Gender Imagesmentioning
confidence: 99%
“…The tractor is therefore a strong masculine symbol (Brandth 1993). Lie (1991Lie ( , 1992 has shown that because technology functions as a symbol of masculinity, it becomes a vital source of masculine gender identity. Machines are a part of the picture men show of themselves, and the machines tell us that the persons are in possession of qualities required for a man (Lie 1992).…”
Section: Technology and Gender Imagesmentioning
confidence: 99%
“…This position therefore also 'queers' the heterosexist assumptions underpinning dualistic notions of the sex/ gender binary . (p. 778) Research has suggested that in STEM educational communities, particularly in engineering, gender discourses are often rigid and may hinder women's acceptance, engagement, and persistence by limiting the identities and actions that are commonsensical in these settings (Henwood, 1998;Lynch & Nowosenetz, 2009;Phipps, 2007;Stonyer, 2002;Wolfe & Powell, 2009) -namely, prevailing heteronormative, gendered discourses connect expertise in science and engineering with masculinity and construct binaries which link incompetence and lack of expertise in science and engineering with femininity (De Welde & Laursen, 2011;Harding, 1991;Lie, 1995;Wajcman, 1991). In Western culture, powerful, culturally gendered disciplinary practices produce docile, feminine bodies: acceptable social positions for women often include displays of "frailty, fear, and incompetence" (Goffman, 1977, p. 312), and these practices become even more pronounced, and reinforced, in the specific institutional context of STEM.…”
Section: Epistemological and Methodological Frameworkmentioning
confidence: 99%
“…Gender symbolism means that the connection between masculinity and technology does not state that technology reflects the capacities of specific (real) men, but more probably images of hegemonic masculinities (Harding 1986, Lie 1995. Masculinity and femininity are abstract frames of reference; they are used when the description of someone's behaviour and skills is made through this frame.…”
Section: Gender Issues In the Ict Fieldmentioning
confidence: 99%
“…The connection is reproduced in everyday practices. For example, when fairly recent descriptions of men with computer were made, the frame of reference included engagement of superior knowledge and intellectual capacities as well as mastering and power that may strengthen a man's masculine image, whereas women with computing science knowledge and computer skills were connected to typewriting and office work (Lie 1995).…”
Section: Gender Issues In the Ict Fieldmentioning
confidence: 99%
See 1 more Smart Citation